1975
DOI: 10.1002/eji.1830050609
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibody populations to oligo‐D‐alanine. VIII. Sequential studies on properties of antibody subpopulations: rate constant, affinity, and isoelectric focusing spectrum

Abstract: Allotypically marked antisera to the hapten oligo-D-alanine were studied over periods up to 10 months in individual mice and in serial transfers of both nonimmune and memory cells to irradiated recipients. Parameters observed were divalent association rate constants, affinity and autoradiography of isoelectric focusing (IEF) spectra. The two allotypic subpopulations of heterozygous mice are shown to be independent with respect to affinity. Association rate constant, affinity, and IEF spectra of the antibody po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This too favours the assumption that apart from the dissociation method used, the charge in the antigenic determinant and the antibody combining site determines whether or not PI and antibody avidity are closely linked. Weiler et al (1975) reported that in one instance anti-oligo-D-alanine antibodies with a low PI showed a markedly low affinity. In the latter case this was presumably due to a mutation of a clone during hyperimmunization.…”
Section: Discussionmentioning
confidence: 98%
“…This too favours the assumption that apart from the dissociation method used, the charge in the antigenic determinant and the antibody combining site determines whether or not PI and antibody avidity are closely linked. Weiler et al (1975) reported that in one instance anti-oligo-D-alanine antibodies with a low PI showed a markedly low affinity. In the latter case this was presumably due to a mutation of a clone during hyperimmunization.…”
Section: Discussionmentioning
confidence: 98%